Public Health, Resilience and Identity Crisis in Children of Families under the Support of Imam Khomeini Relief Committee - Akbar Karami; Hamid Amini Koltapeh; Nasim Noori; Akbar Mahdilou (Journal of Modern Psychology, 2022)
The aim of this study is to investigate the general health, resilience, and identity crisis among children from families supported by the Imam Khomeini Relief Committee, as well as predicting the general health of individuals based on resilience and identity crisis. In this research, 156 male students from the province of Zanjan and the city of Maragheh, who were under the support of the Imam Khomeini Relief Committee, were studied using the Goldberg General Health Questionnaire (GHQ), Connor-Davidson Resilience Scale (CD-RISC), and Rajaei Identity Crisis Scale. The data were analyzed using Pearson correlation and multiple regression analysis. The findings indicated a significant positive relationship between general health and resilience, and a significant negative relationship between general health and identity crisis among these individuals. Furthermore, a significant negative relationship was found between resilience and identity crisis. Multiple regression analysis showed that general health explains a small amount of the variance in resilience and identity crisis in these individuals. This study demonstrated that under conditions of high resilience and low identity crisis, individuals would have better general health.